Apakah Kesetaraan Gender , Pemberdayaan Perempuan Dalam Kewirausahaan Dan Pelatihan Berpengaruh Terhadap Pembangunan Desa Ramah Perempuan Dan Peduli Anak? - Pawestri Winahyu; Jekti Rahayu (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2024)
This research aimed to examine the influence of gender equality and women's empowerment and their influence on entrepreneurship training and the successful development of women-friendly and child-caring villages. The research subjects are women entrepreneurs in Sumberjambe District, Jember Regency. This research is quantitative research with an associative research approach. The research population is woman entrepreneurs in Sumberjambe District, Jember Regency. The research sample was determined by non-probability sampling as many as 95 people. For data analysis, Structural Equation Model (SEM) analysis was conducted with the Partial Least Square / SEM-PLS approach. The results showed that gender equality and women's empowerment had a significant effect on entrepreneurship training. Gender equality and entrepreneurship training have a significant effect on the success of women-friendly and child-caring village development. Meanwhile, women's empowerment does not significantly affect the success of women-friendly and child-caring village development.